Peran Manajemen Sumber Daya Manusia dalam Membangun Psychological Safety sebagai Fondasi Kolaborasi Efektif pada UMKM di Kota Makassar - Saripuddin, Yulia; Hasriani; Az Zahra, Urmila; Muchran, Muchriady (PT Maju Malaqbi Makkarana, 2026)
This study aims to analyze the role of human resource (HRM) management in building a collaborative work culture in MSMEs in Makassar City. A qualitative descriptive approach was used to explore the practices, challenges, and strategies implemented by MSMEs. The research sample was purposively selected based on the criteria of small and medium-sized MSMEs with 10–100 employees and having been operating for at least three years. Data were collected through in-depth interviews with business owners, HR managers, and employees; direct observation in the workplace; and policy documentation and organizational reports. Data analysis was conducted using thematic analysis methods, which included data reduction, grouping by theme, and data triangulation. The results show that MSMEs in Makassar implement strategies such as strengthening internal communication, teamwork training, implementing participatory leadership, and using technology to support collaboration. However, obstacles such as limited resources, individualistic work patterns, and minimal government support remain key challenges. Nevertheless, MSMEs that successfully implement a collaborative work culture demonstrate increased efficiency, innovation, and employee motivation. This study concludes that HRM plays a strategic role in building a collaborative work culture. Leadership support, investment in employee development, and collaboration between teams are the keys to success in increasing the competitiveness of MSMEs.